2016
DOI: 10.1007/s00330-016-4435-y
|View full text |Cite
|
Sign up to set email alerts
|

Using 80 kVp on a 320-row scanner for hepatic multiphasic CT reduces the contrast dose by 50 % in patients at risk for contrast-induced nephropathy

Abstract: • The 80-kVp CT protocol enabled reduction of contrast dose by 50 % • The 80-kVp CT protocol reduced the radiation dose by 25-33 % • There was no degradation in the image quality of the 80-kVp protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 41 publications
3
19
1
Order By: Relevance
“…imaging can improve image quality degradation due to X-ray photon deficiency [175,[178][179][180][181][182][183][184][185][186][187].…”
Section: Rationale Cq6-4mentioning
confidence: 99%
“…imaging can improve image quality degradation due to X-ray photon deficiency [175,[178][179][180][181][182][183][184][185][186][187].…”
Section: Rationale Cq6-4mentioning
confidence: 99%
“…177 Combined use of IR and low tube voltage imaging can improve image quality degradation due to X-ray photon deficiency. 175,178,187 When switching to low tube voltage imaging to reduce the contrast agent volume, it is common to adjust the tube current so that the volume CT dose index will be at the same level as the standard voltage scan (120-kV scan) in order to ensure image quality. There are many types of IR with various manufacturers and generations and differing characteristics.…”
Section: (Minds 2017) Quality Of Evidence: a / Strength Of Recommendamentioning
confidence: 99%
“…The clinical utility of the noise reduction effect in adaptive iterative dose reduction 3D (AIDR 3D) protocol due to the hybrid iterative reconstruction (IR) method is widely known. It was reported that using low tube voltage scanning and AIDR 3D protocol together would enable the reduction of exposure dose and contrast medium volume without compromising image quality when compared with conventional tube voltage scanning [11,12]. However, it is suggested that AIDR 3D images may change in sharpness depending on the subject's physique, and image quality using the IR method requires verification regarding the physique of the patient [13].…”
Section: Introductionmentioning
confidence: 99%